Development of An Audio Frequency Meter with Arduino and MAX4466 Sound Sensor - Jufrida; Hebat Shidow Falah; Nanda Hasbullah Sehab (Postgraduate, University of Mataram, 2023)
Sound is one of the areas of study in physics education. Based on the data, it was found that there were difficulties in students' understanding and misconceptions in studying the concept of sound and its parameters. The aim of this research is to design a sound frequency measuring instrument that can visualize one of the parameters in the sound concept: frequency. The research carried out is a type of development research with a 4D model. The results of this research are a series of sound frequency measuring instruments based on Arduino and a Max4466 sound sensor. The validity of the tool was tested with an average validation value of 0.95 in a very good category. The results of calibration using a tuning fork show that the Audio Frequency Meter can consistently measure sound frequencies with an average measurement deviation of 0.514 Hz. Through the results of this research, it is hoped that it can become a reference in developing practical tools for sound concepts.